Healthy nutrition is an important factor in educating a healthy generation - Nilufar Niyozova (Open Academia, 2023)
This article is devoted to the educated foundations of a healthy diet, describes the importance of educating a healthy generation, and gives a scientific and practical classification of experience.
Keywords: healthy eating; healthy generation; Abu Ali ibn Sina